2018
DOI: 10.1016/j.ahj.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of automated interval measurements by widely used algorithms in digital electrocardiographs

Abstract: Among current-generation computer-based electrocardiographs, clinically small but statistically significant differences exist between ECG interval measurements by individual algorithms. Measurement differences between algorithms for QRS duration and for QT interval are larger in long QT interval subjects than in normal subjects. Comparisons of population study norms should be aware of small systematic differences in interval measurements due to different algorithm methodologies, within-individual interval meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 40 publications
(56 reference statements)
2
43
2
Order By: Relevance
“…In Table 2, we compared the QTcB in our population against that derived from the Swiss study by Kobza et al Kobza's study used the SCHILLER AG ECG software technology system compared to the Phillips ECG software used in our study. There are reported differences in ECG intervals obtained from different automated ECG systems (Kligfield et al, 2018). However, there was still a statistically significant difference observed between the racial groups in our study based on the Phillips ECG software.…”
Section: Limitationscontrasting
confidence: 61%
“…In Table 2, we compared the QTcB in our population against that derived from the Swiss study by Kobza et al Kobza's study used the SCHILLER AG ECG software technology system compared to the Phillips ECG software used in our study. There are reported differences in ECG intervals obtained from different automated ECG systems (Kligfield et al, 2018). However, there was still a statistically significant difference observed between the racial groups in our study based on the Phillips ECG software.…”
Section: Limitationscontrasting
confidence: 61%
“…Moreover, detection of QRS onset is challenging, resulting in disagreement between different algorithms. [25] A physiologically accurate definition of the heart vector origin point is crucial for accurate VCG and ECG measurements. Our algorithm searches for the flattest line within the cardiac cycle to provide a robust and reproducible solution, which is important for accurate detection of QRS, T, and SVG peak vectors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison of leading ECG algorithms revealed significant differences in ECG measurements by ECG manufacturers. [25] Different approaches to beat alignment may be one of the reasons of discrepant results of ECG measurements. Results of our study showed that time-coherent beat construction is the best approach, which preserves the physiological sequence of cardiac activation and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus questionable whether manual measurements should be used on their own or whether it is more reliable to visually check the automatic measurements provided by most of the advanced models of ECG equipment (Hnatkova, Gang, Batchvarov, & Malik, ). Similar to the necessity of having serial ECGs interpreted by the same observer, ECG measurements by different equipment may lead to substantial variability (Kligfield et al, , ). However, since the algorithms used in the commercial equipment are steadily advancing (Green et al, ) their clinical reliability is now probably at least equivalent to fully manual measurements especially if combined with visual verifications to eliminate occasional outliers (Hnatkova et al, ).…”
Section: Consistency Of Morphological Interpretationsmentioning
confidence: 99%
“…It is thus questionable whether manual measurements should be used on their own or whether it is more reliable to visually check the automatic measurements provided by most of the advanced models of ECG equipment (Hnatkova, Gang, Batchvarov, & Malik, 2006). Similar to the necessity of having serial ECGs interpreted by the same observer, ECG measurements by different equipment may lead to substantial variability (Kligfield et al, 2018(Kligfield et al, , 2014. (Hnatkova et al, 2006).…”
Section: Cons Is Ten C Y Of Morpholog Ic Al Interpre Tati On Smentioning
confidence: 99%